Mesenchymal stem cell-based therapy for ischemic stroke. Issue 1 (December 2016) - Anderson, Johnathon; Pham, Missy; Contreras, Zelenia; Hoon, Madeline; Fink, Kyle; Johansson, Henrik; Rossignol, Julien; Dunbar, Gary; Showalter, Megan; Fiehn, Oliver; Bramlett, Charles; Bardini, Renee; et al.
Abstract Ischemic stroke represents a major, worldwide health burden with increasing incidence. Patients affected by ischemic strokes currently have few clinically approved treatment options available. Most currently approved treatments for ischemic stroke have narrow therapeutic windows, severely limiting the number of patients able to be treated. Mesenchymal stem cells represent a promising novel treatment for ischemic stroke. Numerous studies have demonstrated that mesenchymal stem cells functionally improve outcomes in rodent models of ischemic stroke. Recent studies have also shown that exosomes secreted by mesenchymal stem cells mediate much of this effect. In the present review, we summarize the current literature on the use of mesenchymal stem cells to treat ischemic stroke. Further studies investigating the mechanisms underlying mesenchymal stem cells tissue healing effects are warranted and would be of benefit to the field.